Strategi Komunikasi Pemasaran untuk Meningkatkan Brand Awareness pada Brand High-End Raptors Motorsport 4X4 - Theresia Andjani Theodora; Christina Christina (Pusat Riset dan Inovasi Nasional, 2025)
The automotive industry, particulary in the high-end motorsport segment, faces challenges in building strong brand awareness to compete effectively in the market. An appropriate marketing communication strategy is essential to reach consumers and establish a sustainable relationship with the brand. This study aims to analyze the marketing communication strategies implemented by Raptors Motorsport 4x4 based on Philip Kotler’s 5A Model (Awareness, Appeal, Ask, Act, Advocate) in efforts to enchance brand awareness and loyality. The research method used is descriptive qualitative with a case study approach. Data were collected thorugh in-depth interviews, observations, and documentation studies related to the marketing communication practices of Raptors Motorsport 4x4. The constructivist paradigm is employed as a basis for understanding how these communication strategies are constructed and implemented. The theoretical framework is Philip Kotler’s 5A Model, which outlines five critical stages in the consumer journey with a brand. The finding reveals that Raptors Motorsport 4x4 successfully implements an integrated and sustainable communication strategy, starting from creationg awareness through various media, building appeal with exclusive offerings, facilitating consumer inquiries (ask), encouraging purchase actions (act), to fostering advocacy through positive increases brand awareness and builds consumer loyalty in the high-end motorsport segment. This study provides significant contributions to the development of marketing communication strategies that align with modern consumer behavior in the high-end automotive industry.